Roblox master gamer's guide : the ultimate guide to finding, making and beating the best Roblox games! - Pettman, Kevin (London : Carlton Books, 2018)
A guide to Roblox video games including Jailbreak and Hide and Seek Extreme. Provides tips to enable players to get to the top of the leader boards and earn Robux. Also includes information on how to stay safe online while still having fun.
6.3
3-6
Keywords: Roblox (Computing platform) -- Juvenile literature; Video games -- Handbooks, manuals, etc. -- Juvenile literature; Computer adventure games -- Handbooks, manuals, etc. -- Juvenile literature; Roblox (Computing platform); Video games -- Handbooks, manuals, etc; Computer adventure games -- Handbooks, manuals, etc; Handbooks and manuals